Second-step lectotypification of the name Taxus chienii (Taxaceae) - Chen, Xin; Deng, Yunfei (Phytotaxa, 2015)
When the name Taxus chienii W.C. Cheng (Taxaceae) was published, three gatherings (S. Chen 1384, S. Chen 3024, and Y.Y. Ho 3166) were indicated as the types. Recently, Lin & Chao (2007) designated a duplicate of S. Chen 1384 at PE as the lectotype. However, they overlooked that Law (1948) had previously indicated another gathering Y.Y. Ho 3166 as the “type”, effectively lectotypifying the name. According to the Art. 9.17 of the ICN, Law’s lectotypification must be accepted as the first-step lectotypification and, as such, has priority over that by Lin & Cao. Here, a duplicate of Y.Y. Ho 3166 at NAS is designated as the second-step lectotype of the name Taxus chienii.